Infrared printing technique for the security marking of traceability certificates for meat products - Crčić, Dražen (Array, 2020)
The focus of this paper is the introduction of new security elements into the authenticity of information on documents which concern the traceability of products. This article proposes dual marking using the infrared printing technology, which involves differences between the visible and infrared spectrum and separate detection of certain information with an infrared camera. Each meat product is assigned a unique designation, embedded in the document and hidden from the naked eye, in order to prevent changing, scanning or modifying with currently known techniques. A product receives a certificate with a security approval which carries information about the complete traceability of the product. A new central data registry which collects information from all necessary sources is proposed. The web portal and the accompanying database are designed to work in the cloud. The security of the exchange of data between the server and the user is ensured. The information about the traceability and the delineation between the visible and infrared hidden are approved and coordinated by the relevant authorities, breeders, distributors and sellers. The design of the entire information presents completely transparent information about the products to the end consumer.